User Perspective Towards M-banking in Bangladesh: A Case Study Based on University Students - Maliha, Syeeda Raisa; Aziz, Mustafa Nizamul (International Journal of Business and Management Future, 2020)
The focus of this study is on user perspective towards M-banking in Bangladesh and the case study is based on university students. The main purpose of this paper is the opinion of university students based on their preference of bank, time consumption, user-friendly service system, service quality, transaction service charge, the security of transactions and fraudulent activities. Both primary and secondary data have been used in this study. A survey has been conducted with 220 respondents, with a majority of male students where most of the respondents said that M-banking companies should provide more options.  The majority of the respondents also believe that the company provides adequate security about the transaction process, although many students said that they have faced fraud activities with service. Bkash plays a major role in the market because the maximum number of students used Bkash, followed by Rocket, Nagad, etc. Their major concerns about the service revolve around the charges they have to pay and security issues. As the idea of M-banking is a completely new concept for Bangladesh, the opinions of university students can contribute significantly to helping them improve their service.